The Occurrence of Adsorbed Tight Oil and Its Effect on Porosity and Permeability Reduction of Triassic Lacustrine Sandstone Reservoir. (1st July 2022) - Zhou, Qianshan; Li, Xiaotian; Qian, Zhaoming; Chen, Guojun; Lyu, Chengfu; Ma, Xiaofeng; Li, Chao
Abstract : The adsorption of crude oil in the tight sandstone reservoir is significant. Occurrence states of adsorbed tight oil and its pore and throat reduction effect are two significant directions in tight oil exploration and development. In this paper, the occurrence state of adsorbed tight oil and its porosity and permeability reduction effect is systematically analyzed based on a detailed description and discussion of occurrence space, states, changes of porosity and permeability, and its controlling factors. Five occurrence states are recognized based on the differences in spatial location and morphology of adsorbed tight oil. Adsorbed oil is distributed in all kinds of reservoir spaces and primarily concentrated in the pore − throat   radius < 0.25   μ m. The distribution characteristics of reservoir spaces control the occurrence states of adsorbed tight oil. The emulsion form, cluster form, throat form, thin film form, and isolation form are mainly stored in intergranular pores, feldspar dissolved pores, throats, the surface of minerals, and intercrystalline pores, respectively. The massive development of quartz, feldspar, and illite is conducive to the distribution of emulsion form, cluster form, and the throat form of tight oil, while the abundance of clay, especially chlorite, controls the distribution of the thin film form and isolated form of tight oil. The adsorption of tight oil causes clogging in the pore network, resulting in reservoir damage. The adsorption of tight oil in the reservoir leads to increased reservoir density by 0.290 g/cm 3 and the reduction of porosity and permeability by 3.14% and 0.321 × 10 − 3   μ m 2, respectively. And the damage of adsorbed oil to permeability (30.79%) is more severe than that of porosity (19.96%). The effect of pore and throat reduction is more evident in reservoirs with higher content of quartz and feldspar. However, the strong adsorption of clay makes it difficult to separate the tight oil adsorbed on its surface. The nature of adsorbed oil in different occurrence states also can determine the separation efficiency in the extraction process. The adsorbed tight oil with emulsion, cluster, and throat forms is easier to desorb than the isolation and thin film forms. The research results can provide a basis for analyzing the occurrence characteristics and reasonably formulating the development method of tight oil. In addition, it can even provide a new understanding and basis for the densification process of reservoir permeability under different conditions.